Upgrading opportunities in agricultural value chains: Lessons from the analysis of the consumption of processed pineapple products in southern Benin - AOUDJI, KOSSI NOUNAGNON AUGUSTIN; AVOCEVOU, AYISSO CAROLLE MARIELLE; ADEGBIDJI, ANSELME BIENVENU E. ADÉNIYI; GBENOU, ANTOINE SÉRAPHIN; Lebailly, Philippe (My University, 2017)
This study analysed the consumption of processed pineapple products in southern Benin. The low processing of agricultural products does not enable Sub-Saharan Africa to exploit the potential of agriculture for development. The objective of this paper was to identify upgrading opportunities in Benin’s pineapple value chain. A survey was carried out from December 2012 to February 2013 among 250 respondents randomly selected in five cities of southern Benin; and data were collected based on structured interviews. Dried pineapple, jam, syrup, juice, and cocktail were the processed pineapple products available on the market. Beverages, especially the juice, were the main processed pineapple products. The motivations driving the purchase of processed pineapple beverages by consumers were: competitive price and interest for local, natural and therapeutic beverage. There was a margin for the value chain to upgrade products and service, and increase the price while staying competitive. A strong marketing and advertisement campaign is essential to support a wider knowledge of processed pineapple products by consumers. Product traceability is a prerequisite for export in regional and international markets. This makes the certification of the value chain a critical issue. A joint action of value chain stakeholders is needed to exploit these opportunities.
Keywords: consumers; marketing; pineapple; processed products; upgrading; value chain